Remediation of total petroleum hydrocarbons using combined in-vessel composting ‎and oxidation by activated persulfate - A.R. Asgari; R. Nabizadeh; A.H. Mahvi; S. Nasseri; M.H. Dehghani; S. Nazmara; K. Yaghmaeian (Global Journal of Environmental Science and Management)
This study was investigated the efficiency of activated persulfate and ‎in-vessel composting for removal of total petroleum hydrocarbons. ‎Remediation by activated persulfate with ferrous sulfate as pre-treatment was done at batch system. In the chemical oxidation, various variables including persulfate concentrations (10-3000 mg/g as waste), pH (3-7), ferrous sulfate (0.5-4 mg/g as waste)and temperature (20-60°C) were studied. In the biological system, premature compost was added as an amendment. The filter cake to compost ratio were 1:0 (as control) and 1:5 to 15 (as dry basis). C: N: P ratio and moisture content were 100:5:1 and 45-60%, respectively. The results showed that acidic pH (pH=3) had high efficiency for the removal of total petroleum hydrocarbons by activated persulfate. Temperature had the significant effect during the persulfate oxidation. When ferrous sulfate was used as an activator for degradation at acidic condition and 60°C, removal efficiency increased to 47.32%. The results of biological process showed that the minimum total petroleum hydrocarbons removal in all reactors was 62 percent. The maximum and minimum removal efficiency was obtained at 1:5 (69.46%) and 1:10 (62.42%) mixing ratios, respectively. Kinetic study showed that second order kinetic model (R2>0.81) shows the best agreement with the experimental data and the rate of TPH degradation at low mixing ratio (1:3) was faster than high mixing ratio (1:15). Therefore, according to the results, in-vessel composting after pre-treatment by activated persulfate is suggested as an efficient process for degradation of total petroleum hydrocarbons.